Long-Term Impact of Living and Learning at High Altitude: An Altitude Physiology Class for Undergraduate Students - Maurie J. Luetkemeier; John E. Davis; J. Brian Hancock II (Education Sciences, 2022)
Alma College initiated an Altitude Physiology class in 1997 devoted to living and learning at high altitude (3440 m). The class incorporated several key elements of High-Impact Educational Practice including a strong student-research component and collaborative groups assignments. A retrospective survey was administered to alumni of the class to determine its long-term impact. Student responses ranged from “agree” to “strongly agree” with statements regarding the class’s impact on positive learning outcomes such as critical thinking, knowledge acquisition, synthesis of knowledge, and understanding of research. Students generally favored non-traditional formats such as living at altitude for gaining understanding of environmental physiology.